The use of perioperative serial blood lactate levels, the APACHE II and the postoperative MELD as predictors of early mortality after liver transplantation - Basile-Filho,Anibal (2011)
PURPOSE: To evaluate the accuracy of different parameters in predicting early (one-month) mortality of patients submitted to orthotopic liver transplantation (OLT). METHODS: This is a retrospective study of forty-four patients (38 males and 10 females, mean age of 52.2 ± 8.9 years) admitted to the Intensive Care Unit of a tertiary hospital. Serial lactate blood levels, APACHE II, MELD post-OLT, creatinine, bilirubin and INR parameters were analyzed by receiver-operator characteristic (ROC) curves as evidenced by the area under the curve (AUC). The level of significance was set at 0.05. RESULTS: The mortality of OLT patients within one month was 17.3%. Differences in blood lactate levels became statistically significant between survivors and nonsurvivors at the end of the surgery (p<0.05). The AUC was 0.726 (95%CI = 0.593-0.835) for APACHE II (p = 0.02); 0.770 (95%CI = 0.596-0.849) for blood lactate levels (L7-L8) (p = 0.03); 0.814 (95%CI = 0.690-0.904) for MELD post-OLT (p < 0.01); 0.550 (95%CI = 0.414-0.651) for creatinine (p = 0.64); 0.705 (95%CI = 0.571-0.818) for bilirubin (p = 0.05) and 0.774 (95%CI = 0.654-0.873) for INR (p = 0.02). CONCLUSION: Among the studied parameters, MELD post-OLT was more effective in predicting early mortality after OLT.